O bullying a partir de representações sociais de estudantes e da análise de produções científicas - Miranda, Rosane de Sousa (2011)
The general aim of this dissertation was to apprehend the social representations of students about bullying in the school context and the contents which emerges in the scientific literature on bullying. We adopted a psychosocial approach, through the theoretical framework of social psychology, conducted by the Social Representations Theory of Serge Moscovici. The study involved two techniques: field and documentary research. The locus of the field research was a public school located in the city of Joao Pessoa, Paraiba. For documentary research, scientific papers were collected from a web search in two large virtual libraries: SciELO and the Virtual Health Library. The keyword used was "bullying". In field research, two hundred sixty-seven students, mean age was 16 years old, completed a questionnaire containing bio-sociodemographic items and school experiences and the Scale of Aggression and Peer Victimization. Then a subsample was composed, where we seek at least two participants for each level of the variables: age, sex, skin color, body satisfaction the type of involvement whit bullying. Participated in this stage thirty students who responded to a semi structured interview. The contents of the interview was treated by Lexical Analysis of Alceste software through the standard procedure. This computer program was also used for processing the 14 articles collected from the virtual libraries investigated. Data collected through the questionnaire and the scale were analyzed by descriptive and inferential statistics (chi-square). The interview results showed that students represented socially bullying through the anchoring of prejudice targeted to minorities expressed by gays; blame the victim and the normalization of violence, expressed by "jokes" and "laugh" and even in the absence of school and family support, expressed by "lack of good manners" and "taking action". The papers showed a predominance of empirical investigations based mainly on a standard classification of bullying and highlighted the lack of interventions in Brazil. Taken together, the social representations of adolescents and scientific articles's content, was observed that they approach when they refer to the lack of measures and interventions. On the other hand, speeches took distance, as in the case of students, when their lines denoting prejudice associated with bullying (intergroup perspective), while the scientific content signaled for analysis related to correlations with sociodemographic variables (interindividual perspective). These results were discussed within the literature. We also sought to raise the potential limitations of the study, pointing out its applicability and to suggest the unfolding of future research and interventions.